2016
DOI: 10.1371/journal.pone.0166637
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Conjugated Vaccine Reduces the High Mortality for Community-Acquired Pneumonia in the Elderly: an Italian Regional Experience

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is an important cause of illness and death worldwide, particularly among the elderly. Previous studies on the factors associated with mortality in patients hospitalized for CAP revealed a direct association between the type of microorganism involved, the characteristics of the patient and mortality. Vaccination status against pneumococcal disease was not considered. We conducted a retrospective analysis on the mortality rates after a first hospitalization for CAP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
20
0
4
Order By: Relevance
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, childhood vaccination rates against pneumococcal infections correlate poorly with COVID-19 deaths per capita in individual regions of Italy. Baldo, et al (2016) documented the probable reason for this lack of correlation: Italy has, until very recently, relied on the PCV-7 pneumococcal vaccine, which protects against only seven pneumococcal serotypes, rather than PCV-13, resulting in selection for pneumococcal serotypes in Italy to non-vaccinated types and a documented loss of herd immunity for the elderly. Similarly, many regions in Spain not only have very low rates of adult and childhood vaccination but have relied on PCV7 or PCV10 for both groups, again limiting herd immunity against many serotypes (Arencibia Jiménez, et al, 2014;Ciruela, 2018).…”
Section: Hib Is Haemophilus Influenzae Type B Vaccine; Bcg Is Bacillumentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect that could be influenced by studying current trends of infectious sites and their outcome could be researching specific preventative measures tailored towards the most common or highest risk infectious site. Current interventions to prevent certain anatomic site infections are in place such are vaccination against pneumococcal pneumonia or ventilator and line associated bundles [13,14]. Thus, a study directed towards investigating these issues is important for intensive care resource allocation, public health prevention, and helping prioritize future research.…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study from Italy (mean age = 84), 73% of patients had influenza vaccination, and 20% had pneumococcal vaccination. Especially, the protective effect of the new conjugated pneumococcal vaccine on mortality has been emphasized in this study [19]. In the CAPITA trial, pneumococcal vaccine has been shown to be effective in reducing community-acquired pneumonia and invasive pneumococcal disease in individuals aged 65 years and older [20].…”
Section: Discussionmentioning
confidence: 92%